The Influence of Service Quality and Perceived Value on Customer Satisfaction: A Study of Gacoan Noodles Buah Batu, Bandung - Thamrin, Janadi Rammelsbergi; Susilawati Sugiana, Neng Susi; Naysa, Kayla Nazwa; Susanti, Femy; Rohmah, Yunia Nur (Jurnal Digitalisasi Administrasi Bisnis, 2025)
This study aims to explore the influence of service quality and perceived value on customer satisfaction at Gacoan Buah Batu, Bandung. As competition in the food and beverage industry intensifies, understanding key drivers of customer satisfaction has become crucial for business sustainability. The primary objective of this research is to investigate how customers’ perceptions of service quality and value influence their overall satisfaction and dining experience. A qualitative research approach was employed, involving in-depth interviews with 15 respondents who are regular customers of Gacoan. The data were analyzed thematically to identify recurring patterns and insights. Findings indicate that customers place high importance on speed of service, staff responsiveness, cleanliness, and perceived affordability. When these elements meet or exceed expectations, customer satisfaction significantly increases. Conversely, inconsistencies in service or perceived decline in value lead to dissatisfaction. A notable uniqueness of this study lies in its focus on a single outlet, providing a micro-level understanding of consumer behavior in a specific urban setting. The practical implication of this study suggests that Gacoan can enhance customer loyalty by maintaining consistent service quality and optimizing value perception through promotions or personalized experiences. Businesses in similar markets may also benefit from adopting a localized approach to understanding customer needs. These insights serve as a valuable reference for improving service management strategies in Indonesia’s competitive culinary sector. Keywords: Service Quality, Perceived Value, Customer Satisfaction, Qualitative Research, Gacoan Buah Batu